Literature Review: Evaluation of the Performance of the Pharmacy Management Information System (SIM-Farmasi) Using the HOT-Fit Model - Dzakiya Alya Musyafa Satriad; Rasmi Zakiah Oktarlina; Citra Yuliyanda Pardilawati (Lembaga Pengembangan Kinerja Dosen, 2026)
Introduction: The use of information technology has become a necessity and an increasing demand for public service providers, including hospital pharmacy departments. The pharmacy department plays a vital role in supporting patient recovery through the provision of pharmaceutical services oriented toward patient and community needs. To enhance service quality, an effective management information system is required. SIM Farmasi (Pharmacy Management Information System) is designed to improve drug distribution management, ensure medicine availability according to patient needs, and support accurate inventory control. This study applied the HOT-Fit model to evaluate the performance of SIM Farmasi in hospital pharmaceutical services. Methods: This study employed a literature review method by collecting and analyzing previous research articles selected based on predetermined inclusion and exclusion criteria. The selected studies were evaluated and synthesized to strengthen the theoretical foundation, identify knowledge gaps, and support the development of a conceptual framework. Results and Discussion: The effectiveness of SIM Farmasi implementation is strongly influenced by human factors (staff competence and training), organizational factors (management support and standard operating procedures), and technological factors (system quality and data accuracy). Major challenges include limited human resource skills, inadequate system features, and weak organizational policies. Continuous training, system enhancement, and strengthened management commitment are therefore essential to optimize system performance. Conclusion: Overall, the HOT-Fit evaluation indicates that the implementation of SIM Farmasi has not yet been optimal. The main obstacles include insufficient staff training, weak management support, and data accuracy issues within the system.